A CASE OF PORTAL EXTRAHEPATIC AND INTRAHEPATIC THROMBOSIS OF UNSPECIFIED ETIOLOGY, COMPLICATED BY PORTAL HYPERTENSION SYNDROME, ACUTE LIVER FAILURE - Мальцева, Елена Викторовна; Соколовская, Марина Афанасьевна; Братчиков, Дмитрий Юрьевич; Доманская, Ольга Викторовна (Mother and Baby in Kuzbass, 2022)
The article is devoted to the current topic in neonatology – the development of thrombosis. The incidence of neonatal thrombosis and its risk factors are shown. The questions of diagnostics and therapeutic approaches to the development of neonatal thromboses and their results are covered. A clinical case of portal extra/intrahepatic thrombosis of unspecified etiology complicated by the portal hypertension syndrome and acute hepatic insufficiency in a premature infant is presented. The stages of diagnosis and methods of treatment are shown.